Satellites miss environmental priorities: A response to Loveland et al. and Kark et al. - Loarie, S.R.; Joppa, Lucas; Pimm, S.L. (Trends in Ecology and Evolution, 2008)
In response to Loveland and colleagues [1] on our article [2], we commend the job that the USGS has done to operate and manage the tremendously valuable Landsat image data streams and archives. In particular, we applaud plans to implement a 2005 Global Land Survey and to distribute historical Landsat data at no cost. Kark et al. [3] describe the increasingly important participation of additional countries outside the USA in large-scale Earth observation projects. We hope that these programmes will find the international support needed to maintain and distribute archives as cheaply as possible.